Efficacy and tolerability of rufinamide in the treatment of epilepsy (experience of the Svt. Luka’s Institute of Child Neurology and Epilepsy) - K. Yu. Mukhin; O. A. Pylaeva; M. Yu. Bobylova; N. V. Freydkova; L. Yu. Glukhova; M. O. Abramov (Русский журнал детской неврологии)
Background. Despite significant advances in epileptology, approximately one-third of epilepsy patients suffer from drug-resistant seizures. Numerous approaches are currently available to treat epilepsy; however, there are still many patients with treatment-resistant epilepsy, in whom surgical treatment is impossible and alternative methods (vagus nerve stimulation and ketogenic diet) are ineffective. Therefore, searching for novel effective antiepileptic drugs (AEDs) is crucial for these patients.Objective: analysis of own data on the efficacy and tolerability of rufinamide in patients with severe forms of epilepsy and seizures typical of Lennox–Gastaut syndrome (LGS).Materials and methods. The study included 31 patients aged between 4 and 26 years (mean age 7.5 years) that received rufinamide (inovelon). The study cohort comprised 21 males and 10 females. Fifteen patients were diagnosed with LGS, whereas 16 patients were diagnosed with structural focal epilepsy with a phenocopy of LGS. Five patients had an evolution of West syndrome to LGS. The majority of patients (n = 22) experienced predominantly axial tonic seizures and epileptic spasms that were considered as indications for introduction of rufinamide. All patients underwent electroencephalography, video-electroencephalography monitoring during wakefulness and sleep, magnetic resonance imaging (MRI) (including high-resolution MRI with special epilepsy protocols when indicated), genetic examination (tandem mass spectrometry, hereditary epilepsy gene panel test and chromosomal microarray analysis) when indicated, and laboratory tests to assess tolerability of antiepileptic drugs.Results. Good therapeutic effect (more than 50 % reduction in seizure frequency) was achieved in 14 (45.2 %) patients. A less than 50 % reduction in seizure frequency occurred in 5 (16.1 %) patients; in 2 of them seizures became shorter and milder without a significant reduction in their frequency. Rufinamide was ineffective in 9 (29 %) patients. Three (9.7 %) patients experienced aggravation (increased seizure frequency) after the introduction of rufinamide. Thus, treatment with rufinamide was effective in 19 (61.3 %) patients. Rufinamide was well tolerated by most of the patients. Side effects were observed in 6 (19 %) participants. Side effects (forced normalization) caused withdrawal of rufinamide in 1 (3.2 %) patient. Currently, 10 (32 %) patients continue to take rufinamide. Sixteen patients received rufinamide for <6 months, 17 patients – for >6 months, 5 patients – for >12 months, and 1 patient – for >2 years.Conclusion. Our findings are consistent with the results obtained by foreign authors in routine clinical practice. In our study, rufinamide was used only in patients with drug-resistant epilepsy that earlier received many of currently available AEDs (both in monotherapy and in combination with other drugs). All study participants were earlier treated with at least three different AEDs that were ineffective. Seven patients received more than 8 AEDs in various combinations. This initial drug resistance should be taken into account when analyzing the data, which can not be extrapolated to patients with unknown drug resistance. We assume that the early introduction of rufinamide (prior to the detection of drug resistance) might have yielded better results.